COLLABORATIVE STRATEGIC READING (CSR) FOR BETTER READING COMPREHENSION - Impiani Zagoto (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2016)
This article aims to examine the impact of Collaborative Strategic Reading (CSR) strategies on students' reading comprehension. This research type is experiment with quasi experiment design. The data of this research is obtained by reading comprehension test of student of third semester of English education of STKIP Nias Selatan. Data obtained from these tests were analyzed using T-test. Based on the results of data analysis, it was found that t count is larger than ttable. In a sense Collaborative Strategic Reading (CSR) strategy has an impact on students' reading comprehension. Strategy is very helpful for students in determining the main idea and draw conclusions from a text that is read.